Implementasi Kebijakan Pemenuhan Ketersediaan Bahan Baku Industri Perikanan di Wilayah Pesisir Pulau Jawa - Erna Erna (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2021)
The waters of the Java Sea are the most important capture fisheries activity areas in the coastal areas of Java in terms of the number of fishing fleets, the number of fishermen, the number of fishing industries as well as market potential and infrastructure. This study aims to describe the implementation of the policy on the availability of raw materials to meet the fish supply, especially the processing industry. This research method uses cluster analysis. The data taken include secondary and primary data. The results obtained that the policy of fulfilling the availability of fish raw materials can be done by grouping fishing ports based on operational and distribution aspects in the coastal areas of Java. Geographically, the grouping of fishing ports in the coastal areas of Java can be divided into 3 parts, namely the western, central and eastern parts. The grouping is based on the similarity level of fishing port activities. The implementation of the fisheries port connectivity system policy essentially has implications for the fisheries logistics system. The establishment of an integrated fishery logistics system is expected to overcome the problems of shortage of raw materials for the fishing industry, oversupply and decline in the quality of catches.